Peran Mahasiswa Unisri dalam Pemilu - Wulandari, Putri; Trisiana, Anita; Denta W, Valentina; Aji, Dava; Arno N, Dhiwangkara; Poetra W. G, Ahmad (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The purpose of this article's analysis was to examine how students at the University of Slamet Riyadi's perceived the market, particularly focusing on early adopters, starting in 2024. About 60% of the members of the political party consisted of young people, Generation Z, Millennials, and even some students from Universitas Slamet Riyadi. The study took place in November 2023 at UNISRI involving 58 master's students capable of implementing the study's findings regarding the 2024 election. According to the study's findings, there are three factors negatively affecting political views of students at Universitas Slamet Riyadi: the unstable political and social environment, the unstable political environment that affects and shapes actor behavior, the instability of the political structure, and the political environment. These factors shows positive indicators of the students' performance in politics. Notably, the political environment did not negatively affect the situation